Effect of Antenatal Dexamethasone in Late Preterm Period on Neonatal Hypoglycemia: A Prospective Cohort Study from a Developing Country. (24th February 2022) - Pal, Somnath; Sardar, Syamal; Sarkar, Nirmalya; Ghosh, Moumita; Chatterjee, Suparna
Abstract: Objectives: This study compared the risk of hypoglycemia within 72 h of life in infants with and without exposure to antenatal dexamethasone in the late preterm period (34–36 6/7 week's gestational age). Methods: This prospective cohort study was conducted in a tertiary care neonatal unit of Eastern India from May 2021 to November 2021. Babies in the exposed group received at least one dose of antenatal dexamethasone in the late preterm period between 7 days before delivery and birth. 'Complete course' of antenatal steroid was defined as four doses of injection dexamethasone at 12 h intervals and <4 doses were considered as 'Partial course'. Primary outcome was incidence of hypoglycemia within 72 h of life, defined as whole blood glucose <45 mg/dl. Results: Total 298 infants (98 in control, 134 in partial and 66 in complete group) were assessed for final outcome. No significant difference in outcomes were seen in the exposed group compared to unexposed group. However, incidence of hypoglycemia within 72 h (complete vs. partial p= 0.008, complete vs. control p= 0.005) and 12 h of life (complete vs. partial p= 0.013, complete vs. control p= 0.013) was significantly less in complete steroid group. Logistic regression analysis revealed complete course of antenatal corticosteroid significantly decreased the risk of hypoglycemia [adjusted odds ratio, 95% confidence interval (CI) 0.15 (0.03–0.69), p =0.015]. Number needed to be exposed for one additional benefit was 7 (95% CI, 6.35–22.14). Conclusion: Complete course of dexamethasone administered to mothers at risk of late preterm delivery reduces risk of neonatal hypoglycemia within 72 h of life.